Endovascular versus medical management of posterior cerebral artery occlusion stroke: the PLATO study - Nguyen, Thanh N.; Qureshi, Muhammad M.; Strambo, Davide; Strbian, Daniel; Räty, Silja; Herweh, Christian; Abdalkader, Mohamad; Olive-Gadea, Marta; Ribo, Marc; Psychogios, Marios; Fischer, Urs; Nguyen, Anh; et al. (Stroke, 2023)
BACKGROUND: - - The optimal management of patients with isolated posterior cerebral artery occlusion is uncertain. We compared clinical outcomes for endovascular therapy (EVT) versus medical management (MM) in patients with isolated posterior cerebral artery occlusion. - - METHODS: - - This multinational case-control study conducted at 27 sites in Europe and North America included consecutive patients with isolated posterior cerebral artery occlusion presenting within 24 hours of time last well from January 2015 to August 2022. Patients treated with EVT or MM were compared with multivariable logistic regression and inverse probability of treatment weighting. The coprimary outcomes were the 90-day modified Rankin Scale ordinal shift and ≥2-point decrease in the National Institutes of Health Stroke Scale. - - RESULTS: - - Of 1023 patients, 589 (57.6%) were male with median (interquartile range) age of 74 (64-82) years. The median (interquartile range) National Institutes of Health Stroke Scale was 6 (3-10). The occlusion segments were P1 (41.2%), P2 (49.2%), and P3 (7.1%). Overall, intravenous thrombolysis was administered in 43% and EVT in 37%. There was no difference between the EVT and MM groups in the 90-day modified Rankin Scale shift (aOR, 1.13 [95% CI, 0.85-1.50]; P=0.41). There were higher odds of a decrease in the National Institutes of Health Stroke Scale by ≥2 points with EVT (aOR, 1.84 [95% CI, 1.35-2.52]; P=0.0001). Compared with MM, EVT was associated with a higher likelihood of excellent outcome (aOR, 1.50 [95% CI, 1.07-2.09]; P=0.018), complete vision recovery, and similar rates of functional independence (modified Rankin Scale score, 0-2), despite a higher rate of SICH and mortality (symptomatic intracranial hemorrhage, 6.2% versus 1.7%; P=0.0001; mortality, 10.1% versus 5.0%; P=0.002). - - CONCLUSIONS: - - In patients with isolated posterior cerebral artery occlusion, EVT was associated with similar odds of disability by ordinal modified Rankin Scale, higher odds of early National Institutes of Health stroke scale improvement, and complete vision recovery compared with MM. There was a higher likelihood of excellent outcome in the EVT group despite a higher rate of symptomatic intracranial hemorrhage and mortality. Continued enrollment into ongoing distal vessel occlusion randomized trials is warranted.
Gesehen am 13.10.2023